2005
DOI: 10.1520/jai12960
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Bond Strength and Bond Durability of Reactive Powder Concrete

Abstract: This research project aims to use reactive powder concrete, RPC, as a new repair material and evaluate its bond strength and bond durability to existing concrete. One accelerated aging environment, namely a freeze-thaw cycle acceleration deterioration test, was selected for the evaluation of bond durability of the repair materials. Before and after aging, the samples were evaluated by the compressive strength, bond strength (slant shear test), steel pull out strength, and relative dynamic modulus NDT tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Test results from Lee et al [11] revealed that UHPC specimen (5 cm × 10 cm cylinder) was still in good condition after 600 cycles of freezing and thawing in accordance with ASTM C 666-97. After freezing and thawing test, the non-shrinkage high strength mortar showed a reduction in compressive strength, slant shear strength, steel pull out strength, and dynamic modulus by 17, 21, 24, and 25 %, compared with the corresponding values of 6, 7, 5, and 10 %, respectively, for UHPC.…”
Section: Uhpc Precast Concrete Under Severe Freeze-thaw Conditionsmentioning
confidence: 65%
“…Test results from Lee et al [11] revealed that UHPC specimen (5 cm × 10 cm cylinder) was still in good condition after 600 cycles of freezing and thawing in accordance with ASTM C 666-97. After freezing and thawing test, the non-shrinkage high strength mortar showed a reduction in compressive strength, slant shear strength, steel pull out strength, and dynamic modulus by 17, 21, 24, and 25 %, compared with the corresponding values of 6, 7, 5, and 10 %, respectively, for UHPC.…”
Section: Uhpc Precast Concrete Under Severe Freeze-thaw Conditionsmentioning
confidence: 65%
“…HSM showed a reduction in compressive strength, slant shear strength, steel pull out strength, and dynamic modulus by 17, 21, 24, and 25 %, compared with the corresponding values 6, 7, 5, and 10 %, respectively for RPC. For NSC, the average values of relative dynamic modulus of elasticity based on resonant frequencies after 300 and 600 freeze-thaw cycles were 75 and 55 %, compared with the corresponding values of 96 and 92 %, respectively for RPC [13]. Ming-Gin Lee has alsoreported that the effects of compressive and flexural strengthening with bonding RPC of 10 mm thickness are about 200 % and 150 % more than those of NSC.…”
Section: Rpc As a Repair Materialsmentioning
confidence: 92%
“…Ming-Gin Lee evaluated samples with basic composition for compressive strength, bond strength (slant shear test), steel pull out strength, relative dynamic modulus, NDT tests; before and after accelerated aging [13]. Zhang Yunsheng prepared green RPC (C200 GRPC) with compressive strength of 200 MPa.…”
Section: Influence Of Curing Conditionsmentioning
confidence: 99%
“…The following sequence in mixing RPC is based on previous studies (Bonneau et al, 1997;Chan and Chu, 2004;Feylessoufi et al, 2001;Lee and Chisholm, 2005;Morin et al, 2002;Shaheen and Shrive, 2006), as well as our own trial-anderror approaches:…”
Section: Mixing Sequencementioning
confidence: 99%